Republic of Belarus : Social Accountability in Municipal Services - World Bank (Washington, DC, 2014)
The objective of this report is to provide background and context on the housing and utilities sector in Belarus, focusing in particular on Bank-funded Water, Waste management, and biomass-based district heating projects. The report aims to assess the existing Social Accountability (SA) mechanisms in these sectors and in the projects, and identify potential SA entry points and approaches that could be incorporated into the project cycle or in governmental policies and activities. The findings of this report rely on a desk review of legislative and analytical materials on the Water and Waste sectors in Belarus, and on interviews, conducted as part of a mission in April 2013, with Belarusian national and local government representatives, project implementation mangers, civil society groups, and other relevant actors. The structure of the report is as follows. Part one offers an overview of the housing and utilities sector in Belarus and outlines the existing SA mechanisms in the sector. Part two surveys the methodology employed for the preparation of this report. Parts three, four, and five focused respectively on the Bank-funded Water Sanitation and Supply Project, Integrated Solid Waste Management Project, and the Biomass Heating Project. These parts provide an overview of the water, waste, and district heating sectors in Belarus, an overview of each of the projects, and a discussion of existing social accountability mechanisms and challenges in the projects. Lastly, recommendations to enhance SA mechanisms both on the project and on the sector level are provided.